Single‐cell RNA sequencing reveals inflammatory retinal microglia in experimental autoimmune uveitis - Jiangyi Liu; Xingyun Liao; Na Li; Zongren Xu; Wang Yang; Hongxiu Zhou; Yusen Liu; Zhi Zhang; Guoqing Wang; Shengping Hou (MedComm, 2024)
Abstract Autoimmune uveitis (AU) is a kind of immune‐mediated disease resulting in irreversible ocular damage and even permanent vision loss. However, the precise mechanism underlying dynamic immune changes contributing to disease initiation and progression of AU remains unclear. Here, we induced an experimental AU (EAU) model with IRBP651‐670 and found that day[D]14 was the inflammatory summit with remarking clinical and histopathological manifestations and the activation of retinal microglia exhibited a time‐dependent pattern in the EAU course. We conducted single‐cell RNA sequencing of retinal immune cells in EAU mice at four time points and found microglia constituting the largest proportion, especially on D14. A novel inflammatory subtype (Cd74high Ccl5high) of retinal microglia was identified at the disease peak that was closely associated with modulating immune responses. In vitro experiments indicated that inflammatory stimuli induced proinflammatory microglia with the upregulation of CD74 and CCL5, and CD74 overexpression in microglia elicited their proinflammatory phenotype via nuclear factor‐kappa B signaling that could be attenuated by the treatment of neutralizing CCL5 antibody to a certain extent. In‐vivo blockade of Cd74 and Ccl5 effectively alleviated retinal microglial activation and disease phenotype of EAU. Therefore, we propose targeting CD74 and CCL5 of retinal microglia as promising strategies for AU treatment.